Between "You" and "Me": Effects of Pronouns and Order on Disclosing Sexual Assault - Clinton-Lisell, Virginia; Anderson, RaeAnn E. (The Journal of sex research, 2025)
The wording of self-report instruments likely affects its responses; however, there has been very little inquiry into the topic. The purpose of this study was to examine how items in a sexual assault experiences questionnaire varied based on pronouns (first person or second person) and order (sexual-behavior or coercive-tactic first) affected responses. College students (N = 979) were randomly assigned in a 2 by 2 between-subjects experiment to experimental versions of the Sexual Experiences Survey (SES). The findings indicated that the condition with second-person pronouns and coercive-tactic first phrasing had the highest rate of disclosure. Based on reading time results, respondents may have engaged more in processing of items with second-person pronouns or coercive-tactic first phrasing. Moreover, respondents in coercive-tactic first conditions reported more mental effort was required in answering compared to respondents in the sexual-behavior first conditions. There was no effect of condition on negative affect and very little change in negative affect from completing the SES. Overall, the results support the use of second-person pronouns and coercive-tactic first phrasing in sexual assault self-report instruments to support disclosure of this stigmatized crime. Future research should examine how these findings may be extended to other self-report instruments.